Contested languages the hidden multilingualism of Europe - Tamburelli, Marco; Tosco, Mauro (Studies in world language problems ;, 2021)
"This is the first volume entirely dedicated to Contested Languages. While generally listed in international language atlases, Contested Languages usually fall through the cracks of research: excluded from the literature on minority languages and treated as mere ensembles of geographically defined varieties by traditional dialectology. This volume investigates the nature of contested languages, the role language ideologies play in the perception of these languages, the contribution of academic discourse to the formation and perpetuation of language contestedness, and the damage contestedness causes to linguistic communities and ultimately to linguistic diversity. Various situations and degrees of language contestedness are presented and analysed, along with theoretical considerations, exploring potential roads to recognition and issues in language planning that arise from language contestedness. Addressing the "language vs dialect" question head on, the volume opens up new perspectives that are relevant to all students and researchers interested in the maintenance of linguistic diversity"--